Perlindungan Hukum Terhadap Pekerja Debitur Yang Mengalami Pemutusan Hubungan Kerja Akibat Covid-19 Pada Pt.Astra International Tbk-Honda - I Putu Yogi Saputra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Termination of employment during the covid-19 pandemic is a step that must be taken by PT. Astra International Tbk-Honda in order to avoid more severe losses, the legal protection provided to debtor workers who have been laid off during the Covid-19 pandemic has been regulated in Law No. 13 of 2003 concerning Manpower which aims to guarantee all basic rights of workers and guarantee equality and treatment without discrimination on any basis to realize the welfare of workers, especially for workers who have been terminated. The purposes of this research are to reveal the form of legal protection for debtor workers who experience Termination of Employment (PHK) during the Covid-19 pandemic and to study the implications of the government in protecting debtors who experience Termination of Employment (PHK) due to Covid-19. This study uses empirical legal research with a sociology of law approach. The sources of law used are primary and secondary. The techniques for collecting legal materials are recording, summarizing, and quoting techniques and the data that has been collected is then used qualitative analysis techniques. The results of the study reveal that the legal protection provided by the government to workers who have been terminated is by issuing policies in the form of a pre-employment card program and stimulus assistance intended for people who have not worked and workers who have been laid off. The implications of the pre-employment card program policy and stimulus assistance issued by the government were greatly appreciated by one of the workers of PT. Astra International Tbk-Honda who experienced termination of employment, the benefits of the pre-employment card program policy and stimulus assistance were felt to be very helpful in developing the business he had just started.